Best practices in prenatal health promotion: Perceptions, experiences, and recommendations of Ottawa, Canada, prenatal key informants - Nura L Soucy; Rowan M Terrell; Rebecca A Chedid; Karen P Phillips (Women's Health, 2023)
Background: Prenatal health promotion includes the provision of evidence-based information and practical skills to optimize maternal–fetal outcomes. Increasingly, prenatal education is delivered by both healthcare professionals and allied childbirth educators, in community- or hospital-based group classes, targeted outreach programs, and online modules. Objectives: To better understand how prenatal health promotion relates to a diverse urban community, we assessed the perspectives of Ottawa, Canada prenatal key informants. Design: This is a qualitative research with key informant interviews. Methods: Semi-structured interviews were conducted with 11 prenatal key informants, responsible for the design, delivery, or promotion of publicly available prenatal health services. Interviews explored concepts and delivery of prenatal health promotion, strategies to address existing and emerging prenatal topics, identification of barriers to prenatal health services, and recommendations. Results: Key informants recommended a lifespan approach to prenatal health promotion, with an emphasis on healthy behaviors, emotional health, labor and delivery, and postpartum/early parenting. Recognizing community health disparities, key informants used community outreach, and intersectoral collaborations for Indigenous and other at-risk communities to mitigate barriers to prenatal service uptake. Conclusions: Ottawa key informants conceptualized prenatal health promotion as inclusive, comprehensive, and as an extension of preconception, school-based sexual education. Respondents recommended the design and delivery of prenatal interventions as culturally safe and trauma informed, using online modalities to complement in-person activities. The experience and intersectoral networks of community-based prenatal health promotion programs represent potential capacity to address emergent public health risks to pregnancy, particularly among at-risk populations. Plain Language Summary: A broad and diverse community of professionals deliver prenatal education to help people have healthy babies. We interviewed Ottawa, Canada experts in prenatal care/education to learn about the design and delivery of reproductive health promotion. We found that Ottawa experts emphasized healthy behaviors beginning before conception and through pregnancy. Community outreach was identified as a successful strategy to promote prenatal education to marginalized groups.